2015
DOI: 10.1093/bib/bbv025
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the evolutionary conservation between human essential genes, human orthologs of mouse essential genes and human housekeeping genes

Abstract: Human housekeeping genes are often confused with essential human genes, and several studies regard both types of genes as having the same level of evolutionary conservation. However, this is not necessarily the case. To clarify this, we compared the differences between human housekeeping genes and essential human genes with respect to four aspects: the evolutionary rate (dN/dS), protein sequence identity, single-nucleotide polymorphism (SNP) density and level of linkage disequilibrium (LD). The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…A plausible explanation is that since HKs are expressed in all tissues and are relevant for cell survival, mutations in HKs would be evolutionarily selected out. In accordance with this result, it is already known that HKs are more evolutionarily conserved than tissue specific [29, 30].…”
Section: Discussionsupporting
confidence: 81%
“…A plausible explanation is that since HKs are expressed in all tissues and are relevant for cell survival, mutations in HKs would be evolutionarily selected out. In accordance with this result, it is already known that HKs are more evolutionarily conserved than tissue specific [29, 30].…”
Section: Discussionsupporting
confidence: 81%
“…Ideal housekeeping genes or proteins used as internal controls must be expressed constitutively, ubiquitously, and uniformly in cells and tissue, and are not likely to be regulated by any experimental treatment (Tunbridge et al, 2011; Lv et al, 2015). Some recent studies reported that the expressions of several typical internal controls were not stable with the stimulation by pharmacological agents or under special physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Unusual patterns in genetic sequence phylogenies suggest dynamic and relatively recent changes in the evolution of such sequences, implying evolutionarily recent patterns in the way the corresponding HDACs are regulated [49]. In fact, promoter conservation among vertebrate species seems to be more prominent for the ubiquitously expressed HDACs, particularly for HDACs 1 and 2, suggesting that these have not undergone recent evolution, a hypothesis in line with literature on the evolution of so-called “housekeeping” and “essential” genes [50]. Those HDACs that exhibit an unusual pattern of TFBSs on their promoters seem to also have a propensity for expression in fewer tissues such as seen in our results of HDAC5 and their possible preferential association with the cardiovascular/hematopoietic, muscular, nervous and endocrine tissues (Table 2).…”
Section: Discussionmentioning
confidence: 62%